A Theory of Predictive Dissonance: Predictive Processing Presents a New Take on Cognitive Dissonance - Kaaronen, Roope Oskari (Frontiers in Psychology, 2018)
This article is a comparative study between predictive processing (PP, or predictive coding) and cognitive dissonance theory. The theory of cognitive dissonance, one of the most influential and extensively studied theories in social psychology, is shown to be highly compatible with recent developments in PP. This is particularly evident in the notion that both theories deal with strategies to reduce perceived error signals. However, reasons exist to update the theory of cognitive dissonance to one of “predictive dissonance.” Firstly, the hierarchical PP framework can be helpful in understanding varying nested levels of cognitive dissonance. If dissonance arises from a cascade of downstream and lateral predictions and consequent prediction errors, dissonance can exist at a multitude of scales, all the way up from sensory perception to higher-order cognitions. This helps understand the previously problematic dichotomy between “dissonant cognitive relations” and “dissonant psychological states,” which are part of the same perception-action process whilst still hierarchically distinct. Second, since predictive processing is action-oriented, it can be read to support recent action-based models of cognitive dissonance. Third, predictive processing can potentially help us understand the recently speculated evolutionary origins of cognitive dissonance. Here the argument is that responses to cognitive dissonance can instill meta-learning which serves to prevent the overfitting of generative models to ephemeral local conditions. This can increase action-oriented ecological rationality and enhanced capabilities to interact with a rich landscape of affordances. The downside is that in today’s world where social institutions such as science a priori separate noise from signal, some reactions to predictive dissonance might propagate arguably pathological (underfitted, confirmation-biased) mental models such as climate denialism.